Pemanfaatan Pati Umbi Talas (Colocasia Esculenta [L] Schott) untuk Pembuatan Glukosa melalui Proses Hidrolisis Asam sebagai Bahan Baku Produksi Bioetanol - Jonathan P Silalahi; Anerasari M; Erwana Dewi (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Bioethanol can basically be made with basic ingredients in the form of vegetables which contain high starch and carbohydrates such as taro tubers (Colocasia esculenta [L] Schott). The choice of taro in making ethanol is because taro is classified as a tuber like cassava which has 66.8% starch content and 7.2% water content. The process of making glucose is done through acid hydrolysis (HCl) with variations in acid concentration (12, 14, 16, 18, and 20%) and hydrolysis time (1.5; 2; and 2.5 hours). From the analysis, it can be seen that the result of hydrolysis is liquid sugar (glucose) with the highest level of 27.8%brix.